Innovation Marketing: Aspects and Outlook in the Aera of Digitalization - Kuharev, Victoria; Justus Liebig University Giessen (My University, 2025)
Digitalization has not only spurred more innovation but also gave a rise to a new type of innovations: digital innovations (DIs). For such innovations, uncertainty, lack of trust, and privacy concerns are especially acute. Despite these challenges, DIs offer significant potential for firms and start-ups to disrupt existing markets, gain competitive advantage, and encourage consumers to switch from traditional to digital offerings. However, in an attempt to minimize consumer uncertainty, start-ups often model their marketing programs for DIs too closely to those of non-digital alternatives, emphasizing points of parity rather than points of difference. This approach can be counterproductive, as it fails to provide compelling reasons for consumers to adopt DIs over conventional products. Consequently, this underscores the need for a distinct and well-crafted IM approach tailored to DIs.
Keywords: Marketing; Innovation; Digitalisation; Start-Ups; ddc:330